The State’s move to the accrual accounting: theoretical advantages and practical difficulties in application - messai, mohamed (Journal of Research in Finance and Accounting, 2023)
This paper seeks to provide answers to some questions about adoption by the State of accrual accounting, especially those related to the difficulties in adapting this accounting with its particularities, as well as the extent to which it contributes to the improvement of the public management, in the light of the French experience from which Algeria drew its model of accounting reform. The study concluded that the success of this reform was relative in France, with several issues (technical and political in particular) still pending; that is because of the particularities of the public action that make it difficult to apply fully the accounting logic; that Algeria can benefit from France’s experience by taking into consideration those difficulties as it embarked on the implementation of its new accounting system.